2021
DOI: 10.1038/s42003-021-02901-9
|View full text |Cite
|
Sign up to set email alerts
|

Stomach secretes estrogen in response to the blood triglyceride levels

Abstract: Mammals receive body energy information to maintain energy homeostasis. Ghrelin, insulin, leptin and vagal afferents transmit the status of fasting, blood glucose, body fat, and food intake, respectively. Estrogen also inhibits feeding behavior and lipogenesis, but increases body fat mass. However, how blood triglyceride levels are monitored and the physiological roles of estrogen from the perspective of lipid homeostasis remain unsettled. Here, we show that stomach secretes estrogen in response to the blood t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…However, parietal cells use fatty acids to generate energy for estrogen production and acid secretion, so postprandial changes in blood lipid levels and acid secretion activities could affect production of gastric estrogen. 1 Here we show that blood estrogen decreases after meals, especially after carbohydrate intake.Blood fatty acids also decrease, and intravenous injection of lipids partially restores blood estrogen levels. Gastric acid-secreting hormones decrease production of gastric estrogen, while antacid and gastric acid-suppressing hormones, including those secreted after lipid ingestion like glucagon-like peptide-1 (GLP-1), 6 increase gastric estrogen production and postprandially decrease blood estrogen levels.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…However, parietal cells use fatty acids to generate energy for estrogen production and acid secretion, so postprandial changes in blood lipid levels and acid secretion activities could affect production of gastric estrogen. 1 Here we show that blood estrogen decreases after meals, especially after carbohydrate intake.Blood fatty acids also decrease, and intravenous injection of lipids partially restores blood estrogen levels. Gastric acid-secreting hormones decrease production of gastric estrogen, while antacid and gastric acid-suppressing hormones, including those secreted after lipid ingestion like glucagon-like peptide-1 (GLP-1), 6 increase gastric estrogen production and postprandially decrease blood estrogen levels.…”
mentioning
confidence: 54%
“…
Gastric parietal cells secrete estrogen in response to blood lipid (triglycerides and fatty acids) levels. 1 Estrogen decreases blood lipids by suppressing appetite, lipogenesis and lipolysis and by increasing lipid storage and consumption, 2-5 so gastric estrogen plays an important role in maintaining blood lipids levels. However, parietal cells use fatty acids to generate energy for estrogen production and acid secretion, so postprandial changes in blood lipid levels and acid secretion activities could affect production of gastric estrogen.
…”
mentioning
confidence: 99%
“…The results of this study revealed that TGFα serves as the initiating substance for aromatase expression during postnatal development of the rat stomach. Although the importance of estrogen synthesized from the stomach has been suggested [11], this study is a crucially important investigation that elucidates the regulating factor of estrogen in the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been estimated that estrogen secreted from the stomach contributes to the maintenance of hepatic function. However, a recent study highlighted the role of gastric aromatase in using circulating triglycerides as an energy source for estradiol production, suggesting the role of the stomach in monitoring triglyceride levels and shedding new light on the importance of estrogen in the gastric milieu [11]. Despite this accumulated knowledge, the regulatory mechanisms governing gastric aromatase expression remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…These values fall within the reference ranges reported for Japanese quails (Scholtz et al., 2009) and indicate the high hepatic synthesis of fatty acids, cholesterol and phospholipids, which are stimulated by oestrogen and play a critical role in lipid deposition in the yolk of laying hens (Leveille et al., 1957; Salvante et al., 2007; Walzem et al., 1999). Interestingly, in mammals, oestrogen is reported to reduce circulating triglyceride levels via inhibiting feeding behaviour and lipogenesis and promoting triglyceride uptake by adipocytes (Ito et al., 2021). This difference could be attributed to the tendency of females to have higher fat reserves, which is crucial for various fitness components, particularly reproduction, body mass and immunity.…”
Section: Discussionmentioning
confidence: 99%